1973
DOI: 10.4039/ent1051145-8
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF COLD TEMPERATURES ON HATCHING OF THE FOREST TENT CATERPILLAR, MALACOSOMA DISSTRIA (LEPIDOPTERA: LASIOCAMPIDAE)

Abstract: Egg masses of the forest tent caterpillar, Malacosoma disstria Hübner, were collected from new and old infestation areas of northern Minnesota before development started in the spring. Mortality of embryos was recorded after laboratory exposure to −10°, −15°, −20°, −25°, and −30° C for 12, 24, and 72 hours at 1, 2, 3, and 4 days before anticipated hatch. Length of treatment and temperatures of −10° and −15°C had minimal effect on survival. Mortality of embryos varied with days before hatch in an erratic cyclic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 4 publications
0
8
1
Order By: Relevance
“…About 3 days before hatching, pharate larvae withstood temperatures as low as -12°C with little mortality, while about 45% survived temperatures of -18°C for the longest duration, 14 days. These percentages are not directly comparable with those reported by Wetzel et al (1973) because my statistics are reduction in survival while theirs are percentage mortality of pharate larvae within eggs. There is general agreement since they reported the critical spring temperature for forest tent caterpillar pharate larvae under laboratory conditions to be about at -20°C.…”
Section: Discussioncontrasting
confidence: 71%
See 2 more Smart Citations
“…About 3 days before hatching, pharate larvae withstood temperatures as low as -12°C with little mortality, while about 45% survived temperatures of -18°C for the longest duration, 14 days. These percentages are not directly comparable with those reported by Wetzel et al (1973) because my statistics are reduction in survival while theirs are percentage mortality of pharate larvae within eggs. There is general agreement since they reported the critical spring temperature for forest tent caterpillar pharate larvae under laboratory conditions to be about at -20°C.…”
Section: Discussioncontrasting
confidence: 71%
“…These percentages are not directly comparable with those reported by Wetzel et al (1973) because my statistics are reduction in survival while theirs are percentage mortality of pharate larvae within eggs. There is general agreement since they reported the critical spring temperature for forest tent caterpillar pharate larvae under laboratory conditions to be about at -20°C.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Qualitative differences in individuals have also been shown in M. neustria (L.) (Laux 1962;Franz and Laux 1964). Although behavioral polymorphism has been suggested for the economically important M. disstria Hiibner (Campbell 1966;Ives 1973;Wetzel et al 1973), there are no previous reports of behavioral studies on this insect.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, cold spring weather has been blamed for the early-season losses of larvae, presumably through freezing and subsequent death of either foliage or young larvae (Blais et al 1955), and extreme cold winter weather has been blamed for high egg mortality due to freezing (Witter and Kulman 1972). Laboratory experiments have clearly demonstrated that all life-stages are susceptible to cold (Salt 1936;Hanec 1966;Wetzel et al 1973;Raske 1975). Daniel and Myers (1995) used a correlational approach to test whether, in Ontario, large-scale patterns of annual spring or winter weather corresponded with long-term fluctuations in outbreak severity.…”
Section: Introductionmentioning
confidence: 99%